CMT674: Catalyst and Reactor Applications / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (Universiti Teknologi MARA (UiTM), 2020)
The course comprises description of the reactor concept, methods and calculation. The design principles for ideal homogeneous reactors are also introduced It also covers chemical composition and physical properties of catalysts, and catalyst formulation. Students will also be introduced to the synergy of reactor and catalyst application in modern processes.